Managerial Ownership, Capital Structure and Firm Value: Evidence from China’s Civilian-run Firms - Wenjuan Ruan; Gary Tian; Shiguang Ma (Australasian Accounting, Business and Finance Journal, 2011)
This paper examines the influence of managerial ownership on firm performance through capital-structure choices, using a sample of China’s civilian-run firms listed on the Chinese stock market between 2002 and 2007. The empirical results demonstrate a nonlinear relationship between managerial ownership and firm value. Managerial ownership drives the capital structure into a nonlinear shape, but in an opposite direction to the effect of managerial ownership on firm value. The results of simultaneous regressions suggest that managerial ownership affects capital structure, which in turn affects firm value. Our findings imply that the “interest convergence” and “entrenchment” effects of managers’ behaviour in terms of managerial ownership can also explain the agency-relevant situation of China’s civilian-run firms.
Keywords: era2015